Wages for Care Work: COVID-19 and the Public Struggle for Nurses' Wage Equality - Kinnunen Heini (TAYLOR & FRANCIS AS, 2025)
The article examines the news media debate on nurses' wages in Finland during the COVID-19 crisis. By looking at the COVID-19 pandemic in the Nordic context, the study presents the pandemic as a societal context in which the care work burden has increased and the value of care is highlighted. The analysis of the COVID-19 public media debate sheds light on how the struggle over nurses' wages features in this societal context. The study contributes to the research on the gender wage gap related to the economic misrecognition of care work, and the analysis draws from the feminist democratic theoretical concept of the public sphere perceiving the COVID-19 public media as a site for political change-making. My analysis of Finnish news media articles identified three important discourses on the objective of pay rises in the care sector: conveying frontline care professionals' experiences during the pandemic and framing them as an economic-political issue; relying on the ideal of common good in the corporatist debate on care professionals' collective economic interests; and presenting expert analyses of the structural causes behind the gendered segregation of the labour market and the economic undervaluation of care work.